Déjà Experiences in Temporal Lobe Epilepsy. (20th March 2012) - Illman, Nathan A.; Butler, Chris R.; Souchay, Celine; Moulin, Chris J. A.
Abstract : Historically, déjà vu has been linked to seizure activity in temporal lobe epilepsy, and clinical reports suggest that many patients experience the phenomenon as a manifestation of simple partial seizures. We review studies on déjà vu in epilepsy with reference to recent advances in the understanding of déjà vu from a cognitive and neuropsychological standpoint. We propose a decoupled familiarity hypothesis, whereby déjà vu is produced by an erroneous feeling of familiarity which is not in keeping with current cognitive processing. Our hypothesis converges on a parahippocampal dysfunction as the locus of déjà vu experiences. However, several other temporal lobe structures feature in reports of déjà vu in epilepsy. We suggest that some of the inconsistency in the literature derives from a poor classification of the various types of déjà experiences. We propose déjà vu/déjà vécu as one way of understanding déjà experiences more fully. This distinction is based on current models of memory function, where déjà vu is caused by erroneous familiarity and déjà vécu by erroneous recollection. Priorities for future research and clinical issues are discussed.